(3CMcGe GdJCejf hab BNQ GdJYOjdGJ GdJTQjYjI (B:s (3OQGSI ebGQfI (B/s - (3CHh YQGHj, ZGRj NGdOs ((3YeGf(B: s (3OGQ hGFd(B, s, 2011)
(3eGgjI GdJCejf (B: (3GdJYQja HYbhO GdZQQ ,fTCI fXGe GdJCejf h JWhQg h CbSGe GdJCejf h CgOGag , GdGSS GdafjI ddJCejf h VeGfGJg , eOi eTQhYjI YbO GdJCejf aj Gdabg GdGSdGej , GdNWQ GdeDef efg (B: (3eGgjI GdNWQ h TQhWg h bGHdjI GdNWQ ddJCejf h ChUGag , ebGHd GdGJCejf (B"(3GdbSW(B": (3eHOC JfGSH GdbSW eY GdNWQ , GdbSW GdUGaj h YHAGdbSW , COGA GdeDef (B"(3YhV GdJCejf (B" :(3UhQ COGA GdJCejf h cjajI JMOjO ebOGQ COGA GdeDef , GdeUdMI aj GdJCejf ef GdGVQGQ h Ydi GdGTNGU , NUGFU YbO GdJCejf GdYGeI h GdNGUI h GdJQGVj ajg , GfYbGO YbO GdJCejf ef GdfGMjI GdYdejI , GdJRGe GdeDef dg HGdGOdGA HGdHjGfGJ GdeJYdbI HGdNWQ h GdJRGeg HOaY GdbSW (B((3ebGHd GdJCejf (B) (3h cPG GdJRGeg HGNWGQ GdeDef HJMbjb GdNWQ GdeDef efg , GdJRGeGJ GdeDef (B: (3HOaY eHdZ GdJCejf , QLhY GdeDef Ydi GdeSDhdjI Yf GdMGOK , GfbVGA YbO GdJCejf , eQhQ GdReGf GdeGfY ef SeGY GdOYGhi GdfGTFI Yf GdJCejf , eLGd JWHjb GdJCejf GdGRGej h GdCNWGQ GdJj jZWjgG h Mb GdQLhY aj fXGe GdJCejf GdGdRGej Ydi GdeQcHGJ (B.s
Keywords: (3GdJCejf (B- (3GdHfhcs; (3GdJCejf GdGLHGQjs; (3GdJCejf GdHMQjs